1997
DOI: 10.1136/jnnp.63.6.770
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular disorder as a presenting feature of coeliac disease

Abstract: Objectives-To describe the range of neuromuscular disorders which may be associated with cryptic coeliac disease. Methods-Nine patients were described with neuromuscular disorders associated with circulating antigliadin antibodies, whose duodenal biopsies later confirmed the diagnosis of coeliac disease. Neurological symptoms antedated the diagnosis of coeliac disease in all, and most had minimal or no gastrointestinal symptoms at the onset of the neuromuscular disorder. Results-Three patients had sensorimotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 16 publications
2
62
0
6
Order By: Relevance
“…2 Among these extraintestinal manifestations, there is a growing body of publications that report neurologic conditions that are associated with CD. [3][4][5][6][7][8][9][10][11][12] Although earlier studies reported neurologic complications in patients with classical gluten enteropathy, some recent studies report neurologic disorders in asymptomatic CD patients. 13,14 Most of the patients who have CD and were reported as having neurologic manifestations were adults, and these manifestations were usually chronic and "hard," such as epilepsy, 12 cerebellar ataxia, 4,5,13,14 chronic neuropathies, 8,15 myoclonic ataxia, 9 progressive leukoencephalopathy, 7 and dementia.…”
mentioning
confidence: 99%
“…2 Among these extraintestinal manifestations, there is a growing body of publications that report neurologic conditions that are associated with CD. [3][4][5][6][7][8][9][10][11][12] Although earlier studies reported neurologic complications in patients with classical gluten enteropathy, some recent studies report neurologic disorders in asymptomatic CD patients. 13,14 Most of the patients who have CD and were reported as having neurologic manifestations were adults, and these manifestations were usually chronic and "hard," such as epilepsy, 12 cerebellar ataxia, 4,5,13,14 chronic neuropathies, 8,15 myoclonic ataxia, 9 progressive leukoencephalopathy, 7 and dementia.…”
mentioning
confidence: 99%
“…CD can be associated with various neurological diseases such as polyneuropathy, cerebellar ataxia, epilepsy, myelopathy and multifocal leucoencephalopathy [4][5][6][7] . Peripheral neuropathy is one of the most frequent neurological disturbances in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, associa-tion with CD, peripheral neuropathy and neuromuscular disorders has been documented [7] . The relationship between CD and different kinds of myopathies such as dermatomyositis, polymyositis and sporadic inclusion-body myositis, has also been reported [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…The commonest types are symmetrical sensorimotor axonal length dependent peripheral neuropathy and sensory ganglionopathy (Hadjivassiliou et al, 2010b). Other types of neuropathies have also been reported including asymmetrical neuropathy (Kelkar et al, 1996;Hadjivassiliou et al, 1997;Chin et al, 2006) small fibre neuropathy (Brannagan et al, 2005) and rarely pure motor neuropathy (Hadjivassiliou et al, 1997) or autonomic neuropathy (Gibbons and Freeman, 2005). Gluten neuropathy is slowly progressive with a mean age at onset of the neuropathy being 55 years (range 24 to 77) and a mean duration of 9 years (range 1 to 33).…”
Section: Gluten Neuropathymentioning
confidence: 99%